Towards Taking Kiswahili to the Informal Sector: Developing Peoples’ Kiswahili Oral Proficiency as a Soft Skill to Widen their Economic Prospects - Kabale University (Kabale University, 2023)
The investigator, demonstrates sufficient masterly of his area of study, that is, the development and promotion of Kiswahili as a second official language of Uganda as well as a lingua franca throughout the EAC and the Great Lakes Region at large. He relates and locates his study well within the precepts of other relevant and/or recent publications. This helps to identify the knowledge gap, namely sidelining the informal sector in the promotion and use of Kiswahili in Uganda, hence the relevancy of this research proposal which apparently seeks to intervene by involving the informal sector in Kiswahili language promotion and use in Uganda.